2021
DOI: 10.1097/md.0000000000025743
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative omega-3 fatty acids for liver surgery

Abstract: Introduction: The effect of perioperative omega-3 fatty acids for liver surgery remained controversial. We conducted a systematic review and meta-analysis to explore the influence of omega-3 fatty acids versus placebo in patients undergoing liver surgery. Methods: We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through May 2020, and included randomized controlled trials (RCTs) assessing the effect of omega-3 fatty acids versus plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…However, a reduction in the risk of complications was observed only when omega-3 was continuously provided in the perioperative period, rather than in the pre-or post-operative period alone. Additionally, no effects were observed in the cases of mortality, liver failure, biliary leakage, bleeding, or ileus [13]. The methodologically strongest and most recent RCT (n = 261 patients) included in the meta-analysis, conducted by Linecker et al [16], revealed that the intravenous administration of omega-3 perioperatively (100 mL Omegaven) failed to confer protection against post-operative complications after liver surgery.…”
Section: Gastrointestinal and Liver Surgeriesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a reduction in the risk of complications was observed only when omega-3 was continuously provided in the perioperative period, rather than in the pre-or post-operative period alone. Additionally, no effects were observed in the cases of mortality, liver failure, biliary leakage, bleeding, or ileus [13]. The methodologically strongest and most recent RCT (n = 261 patients) included in the meta-analysis, conducted by Linecker et al [16], revealed that the intravenous administration of omega-3 perioperatively (100 mL Omegaven) failed to confer protection against post-operative complications after liver surgery.…”
Section: Gastrointestinal and Liver Surgeriesmentioning
confidence: 99%
“…A meta-analysis conducted in May 2020 on patients who underwent liver tumor surgery revealed that omega-3 was considerably effective in reducing the incidence of postoperative infections [13]. However, a reduction in the risk of complications was observed only when omega-3 was continuously provided in the perioperative period, rather than in the pre-or post-operative period alone.…”
Section: Gastrointestinal and Liver Surgeriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Omega-3 fatty acids (Ω3 FA) supplementation has been explored to ameliorate hepatic steatosis in both animal and human models in the setting of liver disease [154][155][156][157]. In particular, Clavien et al demonstrated that Ω3 FA implementation can ameliorate ischemic/reperfusion injuries in ob/ob mice that undergo 45 min of segmental (70%) hepatic ischemia [154].…”
Section: Clearing Steatosis Prior To Liver Surgerymentioning
confidence: 99%
“…The mechanism may be associated with the competitive inhibition of the proinflammatory property of arachidonic acids (AA) and cytokines by the conversion of EPA and DHA to prostaglandin series 3 (PGE3, PGI3 and TXA3) and leukotrienes series 5 (LTB5, LTC5 and LTD5) 26 27. Therefore, various reports have shown that increasing the ratio of n-3: n-6 PUFAs in the PN emulsion on preoperative or postoperative patients undergoing liver surgery can improve prognosis 28–30…”
Section: Introductionmentioning
confidence: 99%